Organising nursing practice into care models that catalyse quality: A clinical nurse leader case study. (9th February 2018) - Bender, Miriam; Spiva, LeeAnna; Su, Wei; Hites, Lisle
Abstract : Aims: To determine the power of a conceptual clinical nurse leader practice model to explain the care model's enactment and trajectory in real world settings. Background: How nursing, organised into specific models of care, functions as an organisational strategy for quality is not well specified. Clinical nurse leader integrated care delivery is one emerging model with growing adoption. A recently validated clinical nurse leader practice model conceptualizes the care model's characteristics and hypothesizes their mechanisms of action. Methods: Pattern matching case study design and mixed methods were used to determine how the care model's constructs were operationalized in one regional United States health system that integrated clinical nurse leaders into their care delivery system in 2010. Results: The findings confirmed the empirical presence of all clinical nurse leader practice model constructs and provided a rich description of how the health system operationalized the constructs in practice. The findings support the hypothesized model pathway from Clinical Nurse Leader structuring to Clinical Nurse Leader practice and outcomes. Conclusion: The findings indicate analytic generalizability of the clinical nurse leader practice model. Implications for Nursing Management: Nursing practice organised to focus on microsystem care processes can catalyse multidisciplinary engagement with, and consistent enactment of, quality practices. The model has great potential for transferability across diverse health systems.